Digital support and artificial intelligence in cancer patients undergoing radiation therapy: patient utilization, acceptance and attitudes - Springer, Franziska; Hambsch, Peter Kurt; Mehnert-Theuerkauf, Anja; Nicolay, Nils Henrik (Frontiers in Oncology, 2025)
BackgroundNew technologies, such as digital support tools or artificial intelligence (AI) in cancer diagnostics and treatment, offer new possibilities for cancer care. Evidence on patients’ attitudes towards new technologies within the context of cancer care is however very limited to date. We aimed to investigate utilization, acceptance and attitudes towards digital support tools and AI within the context of cancer treatment and to identify associated patient-related factors.MethodsThis exploratory observational cross-sectional study assessed adult cancer patients undergoing radiation therapy with a set of validated questionnaires in addition to newly developed items for this study on acceptance and attitudes towards new technologies within cancer care. Utilization, acceptance and attitudes towards new technologies were assessed descriptively and the impact of associated factors was analyzed using logistic regression models and Analysis of Variance (ANOVA).ResultsIn total, 154 cancer patients were included in our study with a mean age of 63.7 years, 51% were male. In general, patients felt inadequately informed about new technologies, with only 12% feeling informed about digital support tools and 16% feeling informed about AI within their cancer care. One in two patients had used digital support (e.g. websites, apps, wearables). The majority perceived digital support tools as beneficial for all ages (65%) and were open towards the use of AI within their healthcare (79%). Nevertheless, patients reported a strong preference for in-person care, and some patients indicated concerns about possible mistakes by AI (27%). Trust in new technologies revealed a mixed pattern, whereby older patients, those with lower socioeconomic resources, and limited digital health literacy (DHL), were less likely to use digital support (age: p = 0.001, socioeconomic: p = 0.002, DHL: p < 0.001) and reported lower trust in new technologies (age: p = 0.01, socioeconomic: p < 0.001, DHL: p < 0.001) for their cancer care.ConclusionWhile patients are generally open to the use of AI in healthcare, their concerns underscore the need for future research into the physician’s role in ensuring its responsible, safe, and patient-centered utilization. Strengthening DHL, improving information provision, and reducing access barriers for vulnerable groups may enable a more effective integration of new technologies into routine cancer care.